Find the sum of all positive integers such that is divisible by for all positive integers
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
We will show that all odd integers between 1 and 100 inclusive work, and only these values work. Indeed, if k were even, then we can take n = 2 as a counterexample.
Suppose k were an odd integer. Let N = 1 + 2 + 3 + ⋯ + n 1 k + 2 k + 3 k + ⋯ + n k . We want to show that N is an integer. Using the formula for the sum of the first n positive integers, we get
N = 2 n ( n + 1 ) 1 k + 2 k + 3 k + ⋯ + n k = n ( n + 1 ) 2 ( 1 k + 2 k + 3 k + ⋯ + n k ) .
Now, we split into cases based on the parity of n :
Case 1: n = 2 a , for some positive integer a
We have
N = 2 a ( 2 a + 1 ) 2 ( 1 k + 2 k + 3 k + ⋯ + ( 2 a ) k ) = a ( 2 a + 1 ) 1 k + 2 k + 3 k + ⋯ + ( 2 a ) k .
Since k is odd, we have p k + ( ( 2 a + 1 ) − p ) k ≡ 0 ( m o d 2 a + 1 ) and p k + ( 2 a − p ) k ≡ 0 ( m o d a ) , for all positive integers p between 1 and 2 a inclusive. Thus,
1 k + 2 k + 3 k + ⋯ + ( 2 a ) k ≡ ( 1 k + ( 2 a ) k ) + ( 2 k + ( 2 a − 1 ) k ) + ⋯ + ( a k + ( a + 1 ) k ) ≡ 0 ( m o d 2 a + 1 ) ,
and
1 k + 2 k + 3 k + ⋯ + ( 2 a ) k ≡ a k + ( 2 a ) k + ( 1 k + ( 2 a − 1 ) k ) + ( 2 k + ( 2 a − 2 ) k ) + ⋯ + ( ( a − 1 ) k + ( a + 1 ) k ) ≡ 0 ( m o d a ) ,
so we conclude that N is an integer.
Case 2: n = 2 a + 1 for some nonnegative integer a
We have
N = ( 2 a + 1 ) ( 2 a + 2 ) 2 ( 1 k + 2 k + 3 k + ⋯ + ( 2 a + 1 ) k ) = ( a + 1 ) ( 2 a + 1 ) 1 k + 2 k + 3 k + ⋯ + ( 2 a + 1 ) k .
Similar to the n even case, we have p k + ( ( 2 a + 2 ) − p ) k ≡ 0 ( m o d a + 1 ) and p k + ( ( 2 a + 1 ) − p ) k ≡ 0 ( m o d 2 a + 1 ) , for all positive integers p between 1 and 2 a + 1 inclusive. Thus,
1 k + 2 k + 3 k + ⋯ + ( 2 a + 1 ) k ≡ ( a + 1 ) k + ( 1 k + ( 2 a + 1 ) k ) + ( 2 k + ( 2 a ) k ) + ⋯ + ( a k + ( a + 2 ) k ) ≡ 0 ( m o d a + 1 ) ,
and
1 k + 2 k + 3 k + ⋯ + ( 2 a + 1 ) k ≡ ( 2 a + 1 ) k + ( 1 k + ( 2 a ) k ) + ( 2 k + ( 2 a − 1 ) k ) + ⋯ + ( a k + ( a + 1 ) k ) ≡ 0 ( m o d 2 a + 1 ) ,
so N is an integer.
Therefore, 1 + 2 + 3 + ⋯ + n ∣ 1 k + 2 k + 3 k + ⋯ + n k when k is odd. This gives us a final answer of 1 + 3 + 5 + ⋯ + 9 9 = 2 5 0 0 .